(untitled) (Scottish Historical and Archaeological Internet Reports, 2006)
This paper presents the results of a series of excavations carried out by the City of Edinburgh Council Archaeology Service between 1990 and 1992 in advance of the Edinburgh Park development (NGR: NT 178 720). Following a programme of test excavations, seven areas were opened up for excavation. Three of these contained significant archaeology dating to the Neolithic, Bronze and Iron Ages. The main findings included a Neolithic trackway, evidence for Bronze Age settlement and a large stone-built structure dating to the beginning of the 1st millennium AD.